Motivations and strategies in retranslating the Anglo-Saxon Chronicle - Dean, Thomas (fi=Turun yliopisto|en=University of Turku|, 2018)
The aim of this thesis is to study three different translations of the Anglo-Saxon Chronicle into Modern English. These are E. E. C. Gomme’s, G. N. Garmonsway’s and Michael Swanton’s translations. The purpose is to find out how the translations differ and why. The translations are compared with each other first in a general way and after that certain aspects are studied more closely. The results show that the main reason these translations of the same work differ from each other is because of the personal preferences of the translators rather than errors in older translations, although that is also a smaller cause of differences. Also, many parts of the Anglo-Saxon Chronicle that are difficult to translate were identified and the ways to translate them were detailed in the study.